PENERAPAN CORPORATE GOVERNANCE DAN DAMPAKNYA TERHADAP KINERJA KEUANGAN PERUSAHAAN - Devy, Tartila (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aims to determine the effect of the implementation of Corporate Governance on the financial performance of manufacturing companies listed on the Indonesia Stock Exchange in 2018-2021. The population in this study was 181 companies, and companies that met the criteria in the study were 13 companies. So the total research sample is 52 samples. The data analysis methods used are: Classical Assumption Test consisting of: Normality Test, Multicollinearity Test, Heteroscedasticity Test and Autocorrelation Test. The data analysis techniques used are Descriptive Statistical Analysis and Multiple Linear Regression Analysis. The results of the research show that there is no significant influence between Corporate Governance on financial performance.